Evaluation of the impact on dams in the previous and current scenario in affected areas - Heinen, Gabriela de Vargas; Cardoso Sobrinho, José (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2024)
Precision agriculture and irrigation improve yields and efficiency in agricultural activity. It is important to consider the impact of irrigation on the environment and adopt mitigation solutions. In this work, a regression equation model for remote prediction of environmental impact caused by the construction of irrigation dams in the micro watersheds of the Ijuizinho River/RS was developed through quantitative data. For this, 20 dams were selected in the study area, where a history of construction and maintenance was informed. Two buffers were drawn around the dams, considering the minimum PPA required for dams following current environmental legislation, Law Number 12.651/2012 and CONSEMA Resolution nº 323/2016. To carry out the spatial analysis of land use and occupation, images from the Sentinel-2A sensor were selected. The pre-processing of images was carried out following supervised classification to determine the land use classification. The information was used to obtain the proportion of each type of habitat present in the study area, namely: water, tillage, arboreal vegetation, damp areas, and undergrowth. For the analysis of environmental impact, equations of modeling were realized using multiple linear regression and Pearson’s correlation. Currently, there are no forms of prior analysis to define the environmental impact caused by the construction of an irrigation dam. Prior analysis of the environmental impact would be an important tool for decision-making on environmental licensing. The proposed methodology does not replace the other licensing steps but may justify their starts. Based on the present data set and statistical analyses applied, developing models to predict the environmental impact was not possible. Therefore, it is important to consider the peculiarities and importance of each habitat in the watershed. The suppression of a stable habitat for the construction of a dam, even with PPA recovery, will cause an environmental impact.